1990
DOI: 10.1080/00224545.1990.9924565
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Unrealistic Optimism

Abstract: Substantial evidence suggest that people tend to be unrealistically optimistic that positive events will happen to them and that negative events will not. However, recent research indicates that under certain conditions they may be unrealistically pessimistic. Variations in the levels of optimism and pessimism experienced towards events are generally given cognitive explanations. A relation between optimism and pessimism and anxiety, a variable related to emotion as well as cognition, was investigated in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0
2

Year Published

1994
1994
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 8 publications
3
12
0
2
Order By: Relevance
“…Looking at our results, showing the dynamics of unrealistic optimism in our participants, one can (optimistically!) risk the statement days earlier as an indicator of an increase in awareness of the existing danger, then the simultaneous belief that others are even more exposed than oneself may have positive consequences-this may be associated with a lack of excessive anxiety, leading to passivity [22,23] and motivate engagement in health promoting activities [18]. Of course, we must stress that this is only supposition on our part, unsupported by empirical evidence.…”
Section: Discussionmentioning
confidence: 97%
“…Looking at our results, showing the dynamics of unrealistic optimism in our participants, one can (optimistically!) risk the statement days earlier as an indicator of an increase in awareness of the existing danger, then the simultaneous belief that others are even more exposed than oneself may have positive consequences-this may be associated with a lack of excessive anxiety, leading to passivity [22,23] and motivate engagement in health promoting activities [18]. Of course, we must stress that this is only supposition on our part, unsupported by empirical evidence.…”
Section: Discussionmentioning
confidence: 97%
“…In many other studies, risks for different negative outcomes are analyzed separately, but risks for different outcomes are not directly compared and whatever differences are found are not discussed in detail, (Dewberry, Ing, James, Nixon, & Richardson, 1990;Peterson & DeAvila, 1995). For example, Weinstein (1987, p. 494) stated that "unrealistic optimism is prevalent in the population as a whole" Kulik and Mahler (1987, p. 24) suggested that "participants overall demonstrated a pervasive tendency to view their own risk for a variety of negative life events as significantly below average."…”
Section: Implications Of the Dimensionality Of Unrealistic Optimism Fmentioning
confidence: 99%
“…The rationales used in many other studies have not been so detailed. In some studies, problems were chosen because they had evoked an optimistic bias in past research (Kulik & Mahler, 1987;Perloff & Fetzer, 1986;Weinstein, 1983); whereas in others no specific rationale was provided (Cohn et al, 1995;Dewberry et al, 1990;Hoorens & Buunk, 1993;Peterson & De Avila, 1995;Weinstein, 1984Weinstein, , 1987.…”
Section: Implications Of the Dimensionality Of Unrealistic Optimism Fmentioning
confidence: 99%
“…Other studies indicate that anxious individuals exhibit either reduced optimism or pessimistic responses (e.g. Dewberry, Ing, James, Nixon & Richardson, 1989;Norem & Cantor, 1986) and optimism is related to internal locus of control (Hoorens & Buunk, 1993).…”
mentioning
confidence: 99%